(untitled) - Baietti, Aldo (Washington DC, 2005)
The small share of private participation in the water supply and sanitation (WSS) sector and the extremely low level of risk mitigation instruments underscore (a) the specific nature of the risks affecting the sector; (b) the lack of adequate project preparation (and thus of bankable projects); (c) the difficult access of water investments to financial markets; and (d) the constraints and limitations among the various risk mitigation instruments, which render them inadequate to respond in a significant way to the challenges of the water sector. Given these serious impediments, it is no surprise that despite the urgent need for risk alleviation, the effective demand for risk mitigation products has been lacking. This paper focuses on ways to better connect water sector investments with financial markets and to adapt risk mitigation instruments correspondingly.
Keywords: Water supply,Sanitary engineering,Cung cấp nước,Kỹ thuật vệ sinh; Management,Quản lý